Cell-derived nanoplatforms for cancer therapy - Lins, Paula Maria Pincela (2021)
Nanomaterials are promising platforms for cancer therapy due to their innate passive targeting. The success of nanomaterials into the clinics depends on their blood circulation time and accumulation in the target tissue, factors related with their ability to evade the immune system. Cell-derived nanoplatforms are an emerging technology to enhance the delivery by active targeting the tumor site, without the perks of chemical conjugations. In this thesis we report the development of biomimetic novel platforms using the cell-derived technology and their in vitro interaction in cells from tumor microenvironment. To understand of the cell-derived nanoplatforms, two different nanomaterials were synthesized and further coated with extracellular vesicles and cell membrane extract from two different cell lines. First, gold nanorods (AuNRs) were coated with two macrophage derived vesicles, cell membrane extract and extracellular vesicles. Cell membrane-coated AuNRs interacted more with the metastatic cancer cells and the extracellular vesicles interacted more with the source cells. The main difference evaluated among the coatings was the presence of the tetraspanin CD47, an immunosuppressive marker for phagocytosis. Furthermore, we developed a paclitaxel-loaded polymeric nanoparticle carrier coated with metastatic breast cancer cell membrane. All cell lines showed a preferential uptake for the nanoparticles coated with the cell membrane, with stronger interaction with the source cell and the fibroblasts. Our results pointed to the role of adhesion molecules in the homotypic bind to cancer cells and the interaction with stroma cells as a heritage of the tumor progression pathways. As a consequence of the enhanced interaction of the nanocarriers with fibroblasts, the nanoparticles were significantly cytotoxic. We also explored the tunability of the plasmonic band in relation to their composition and size and evaluated basic culture parameters for extracellular vesicles isolation by means of size distribution and concentration.